POTENSI PENGEMBANGAN OBYEK WISATA PANTAI TAPANDULLU DI KABUPATEN MAMUJU - Heryati, Yati (LPPM Universitas Muhammadiyah Mamuju, 2019)
Culture and natural beauty are valuable assets that have been able to suck up domestic and foreign tourists to come and visit to enjoy the beauty of nature and to study the cultural diversity of the Indonesian people. Tourism has now become a necessity for people at various levels not only for certain circles, so the handling must be done seriously and involve relevant parties, in addition to achieving all the objectives of tourism development, promotion must be held so that the potential and attractiveness tourism can be better known and able to move potential tourists to visit and enjoy tourist attractions. The Tourism Object of Tapandullu Beach in Mamuju Regency is the most visited tourist object of Mamuju people so far, where the strategic location is not too far from the center of the crowd, so that holidays are widely used by Mamuju people and visitors who are outside the city.